A multi-stimuli responsive tetraphenylethene derivative: Self-reversible mechanochromism, mechanoluminescence, switchable photochromism. (March 2021) - Zhang, Hongyan; Li, Wenlang; Huang, Qiuyi; Huang, Guangxi; Chi, Zhenguo; Li, Bing Shi
Abstract: Most of the reported stimuli-responsive aggregation induced emission (AIE) molecules are single-functioned and it remains highly demanded to integrate multi-stimuli responsive properties in one molecule. A multi-stimuli responsive TPE derivative 1 was synthesized bearing multiple properties including mechanochromism, mechanoluminescence and photochromism. Mechanoluminescence was only shown by the single crystal form, while photochromism was only observed in the amorphous powder. The mechanochromic property of 1 was self-reversible, but can also be accelerated by thermal or solvent vapor treatment. The photochromic property of 1 was easily switched on by a phase transition from crystalline state to amorphous state upon grinding. By a combination of mechanochromism and photochromism, a two-step procedure of color response of 1 was demonstrated upon grinding and UV irradiation. This novel molecule provides an important insight to the development of multi-stimuli responsive materials and advanced anti-counterfeiting materials. Graphical abstract: A multi-stimuli responsive TPE derivative was demonstrated as a novel anti-counterfeiting material. Image 1 Highlights: TPE derivative 1 could display multi-stimuli responsive properties: mechanochromism, mechanoluminescence and photochromism. The mechanochromic and gated photochromic properties of 1 made it a promising anti-counterfeiting material. A two-step procedure of color change of 1 was demonstrated to show its application in anti-counterfeiting.